From Linear to Networked: The Paradigm Revolution and Industrial Reconstruction of Documentary Interactive Communication in the Era of Digital Intelligence (Journal of science and technology exploration, 2026)
In the era of digital intelligence, the deep integration of digital technologies and artificial intelligence has reconstructed the media ecosystem, leading to a profound transformation in documentary communication modes from linear, one-way transmission to networked, bidirectional interactive communication. Based on the theoretical framework of interactive communication and incorporating typical domestic and international cases as well as industry practices, this paper systematically explores the internal mechanisms, technological support, and practical pathways of documentary interactive communication. The study finds that interactive documentaries achieve a dynamic balance among "communicators-content-users" through nonlinear narrative structures, multimodal interactive interfaces, and user-participatory creation. However, they face challenges such as technological adaptability, content ethics, and commercial sustainability. The research proposes a "technology-content-user" three-dimensional collaborative strategy to provide theoretical support and practical references for the digital transformation of the documentary industry.
Keywords: Era of digital intelligence; Documentary; Interactive communication; Industrial reconstruction